Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan di Kabupaten Kudus - Maulana Mahrus Syadzali (Jurnal Ilmiah Ekonomi Islam, 2020)
The purpose of this study explains: 1) the influence of service quality on customer satisfaction, 2) the influence of Store Image on customer satisfaction, 3) the effect of price on customer satisfaction, 4) test service quality, store image and price on customer satisfaction in UD Menara 05 Kudus. This research is a field research with a quantitative description. Data collection was carried out by free guided interviews, participatory observation, and documentation. Furthermore, the researcher conducted the validity of the data with the model of extension of observations, increasing persistence, triangulation, member checks, and peer discussion. The results showed that the influence of service quality, store image and price on customer satisfaction in Kudus is good and optimal. Because it is supported and encouraged from the company and within the family. In terms of service quality, the quality in UD Menara 05 Kudus is categorized as sufficient, Store Image is in the sufficient category, and Prices are categorized as good for customer satisfaction